2017
DOI: 10.1016/j.visres.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Global motion perception is related to motor function in 4.5-year-old children born at risk of abnormal development

Abstract: Global motion perception is often used as an index of dorsal visual stream function in neurodevelopmental studies. However, the relationship between global motion perception and visuomotor control, a primary function of the dorsal stream, is unclear. We measured global motion perception (motion coherence threshold; MCT) and performance on standardized measures of motor function in 606 4.5-year-old children born at risk of abnormal neurodevelopment. Visual acuity, stereoacuity and verbal IQ were also assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 84 publications
8
26
0
Order By: Relevance
“…Also in agreement with our data from 4.5 year old children [8], when controlling for language score, we observed that stereopsis was associated with fine and composite motor scores whereas binocular visual acuity was not significantly associated with any of the motor scores. These results reinforce the importance of binocular vision for the development of fine motor skills, and demonstrate that stereopsis and fine motor function are associated early in childhood.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Also in agreement with our data from 4.5 year old children [8], when controlling for language score, we observed that stereopsis was associated with fine and composite motor scores whereas binocular visual acuity was not significantly associated with any of the motor scores. These results reinforce the importance of binocular vision for the development of fine motor skills, and demonstrate that stereopsis and fine motor function are associated early in childhood.…”
Section: Discussionsupporting
confidence: 92%
“…The similarity between the results we report here for 2 year old children and those we reported previously for 4.5 year old children [8] is striking. In both studies, motion coherence thresholds were modestly but significantly associated with both gross motor and overall motor function, even when controlling for general cognitive ability, as indicated by Bayley-III language scores.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations